Analytical assessment of torque and stator currents of an induction motor due to voltage sags - Vijaya Huchche; Nita Patne (Institute of Advanced Engineering and Science, 2023)
Voltage sag is a frequently encountered phenomenon in a power system to which many three phase induction motors are directly connected. This paper presents a simple analytical method for calculation of net electro-magnetic torque and stator currents of an induction motor subjected to symmetrical as well as unsymmetrical sags in supply voltage. This work presents an innovative path to compute net electro-magnetic torque and increase in stator currents for all seven types of sags using the well-known symmetrical component theory. Such a simple method and expressions used in this paper are not reported in the literature reviewed so far. The computation is further extended for different load conditions while varying the symmetrical sag magnitude. The simplicity of analytical assessment of loading effect on electro-magnetic torque from no-load to full-load condition for all sag types is presented. The outcome of the study was verified by imitating the environments for various types of sag in MATLAB/Simulink. The observations are that the average output torque of a motor decreases and ripple in power increases during unsymmetrical sags.